Strengthening the governance of food systems for nutrition in Africa: a political economy analysis of food policy in South Africa and Ghana - Anne Marie Thow; David Neves; Robert Aidoo; Linda Nana Esi Aduku; Busiso Moyo; Charles Apprey; Florian Kroll; Reginald Annan (Cambridge University Press, 2024)
Abstract Objective: To examine underlying political economy factors that enable or impede the integration of nutrition considerations into food system governance. Design: Comparative political economy analysis of data collected through (1) value chain analyses of selected healthy and unhealthy commodities and (2) food system policy analyses, using a theoretical framework focused on power, politics, interests and ideas. Setting: Ghana and South Africa. Participants: Value chain actors relevant to healthy and unhealthy foods (Ghana n 121; South Africa n 72) and policy stakeholders from government (Health, Agriculture, Trade and Industry, Finance), academia, civil society, development partners, Civil Society Organization (CSO) and private sector (Ghana n 28; South Africa n 48). Results: Nutrition was a stated policy priority in both countries; however, policy responsibility was located within the health sector, with limited integration of nutrition into food system sectors (including Agriculture, Trade and Industry). Contributing factors included a conceptions of policy responsibilities for nutrition and food systems, dominant ideas and narratives regarding the economic role of the food industry and the purpose of food system policy, the influence of large food industry actors, and limited institutional structures for cross-sectoral engagement and coordination. Conclusions: Integrating nutrition into multi-sectoral food policy to achieve multiple food system policy goals will require strategic action across jurisdictions and regional levels. Opportunities included increasing investment in healthy traditional foods, strengthening urban/rural linkages and informal food systems, and strengthening institutional structures for policy coherence and coordination related to nutrition.